Cationic palladium(ii) complexes as catalysts for the oxidation of terminal olefins to methyl ketones using hydrogen peroxide1. Issue 5 (12th May 2015) - Cao, Qun; Bailie, David S.; Fu, Runzhong; Muldoon, Mark J.
<x xml:space="preserve">Abstract</x> Ligated Pd(ii) complexes have been studied for the catalytic oxidation of terminal olefins to their corresponding methyl ketones.